(untitled) (Journal of the College of Basic Education, 2023)
In this paper, we will prove some fixed point theorems for single valued self contractive mapping satisfying special conditions in complete cone metric space by using a vector valued altering function (Ms-function) with the assumption that the Cone is not normal. Our results generalize some recent results.